The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1108/03074800710735311
|View full text |Cite
|
Sign up to set email alerts
|

Users' behaviour patterns in academic libraries' OPACs: a multivariate statistical analysis

Abstract: Purpose-This paper aims to present real time user searches in a Greek academic library OPAC (University of Macedonia Library) in relation to user profile. Design/methodology/approach-Using as a test bed a Greek academic library and its OPAC's transaction logs along with a system implanted questionnaire, data were gathered, processed and analyzed using multivariate statistical analysis techniques. Findings-In making a synthesis of the analyzed data, a series of questions related to everyday library work were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…Similar results were reported by Lau and Goh (2006), Malliari and Kyriaki-Manessi (2007), Antell and Huang (2008), Coonan (2008), Hunter (2011) and Schlembach et al (2013). These studies revealed that OPAC users prefer to search for known items such as title, name of author and keywords.…”
Section: Related Studiessupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results were reported by Lau and Goh (2006), Malliari and Kyriaki-Manessi (2007), Antell and Huang (2008), Coonan (2008), Hunter (2011) and Schlembach et al (2013). These studies revealed that OPAC users prefer to search for known items such as title, name of author and keywords.…”
Section: Related Studiessupporting
confidence: 92%
“…These three search options accounted for over 83% of all search queries. Preferences for title, author and keyword search options have also been reported in other studies such as Kyriaki-Manessi (2007); and Vorster (2012). However, in this respect this study contrasts with results reported by other studies such as Villén-Rueda et al (2007), Lau and Goh (2006), Antell and Huang (2008), Coonan (2008), Hunter (2011) and Schlembach et al (2013), which established that users prefer to search for known items mainly by author and title.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…And many students prefer to use search engines to conduct their searches (Urquhart et al, 2005), using them frequently—Google in particular (Urquhart & Rowley, 2007). Familiarity, along with experience, in using OPACs is also important for the quality of the searches performed (Malliari & Kyriaki‐Manessi, 2007). Not only do students choose familiar resources, but some students have been found to be unwilling to try the unfamiliar unless it is required (Urquhart & Rowley).…”
Section: Background and Rationalementioning
confidence: 99%
“…In the field of library and information studies (LIS), spelling in OPAC searching has been examined primarily to determine the number of bibliographic records that contain typographical errors (e.g., Beall & Kafadar, 2007; Randall, 1999), or it has been treated mainly as a typographical input error similar to improper search syntax, rather than a more substantive user issue (e.g., Yee, 1991). When spelling has been examined in studies of users' searching behaviors, this has typically occurred through transaction log analysis of OPAC searches that examine the frequency of misspellings (e.g., Blecic, Dorsch, Koenig, & Bangalore, 1998; Blecic et al, 1999; Drabenstott, & Weller, 1996a; Drabenstott & Weller, 1996b; Malliari & Kyriaki‐Manessi, 2007), rather than studies of the individuals themselves who are making the mistakes.…”
Section: Introductionmentioning
confidence: 99%